Cascade synthesis of 5-(Acetoxymethyl) furfural from carbohydrates over Sn-mont catalyst - Shinde, Suhas; Deval, Kashmira; Chikate, Rajeev; Rode, Chandrashekhar (ChemistrySelect, 2018)
The 5-(Acetoxymethyl)furfural (AcMF) is emerged as an important alternative for 5-(hydroxymethyl)furfural (HMF). It is also a starting material for those products which are typically prepared from HMF. The growing importance of AcMF encouraged us to prepare it directly from cheap and abundant carbohydrates. The production AcMF from glucose and glucose-like carbohydrates is an exigent assignment, owing to tough isomerisation of glucose to fructose. The Sn-Mont catalyst having a unique combination of Lewis as well as Bronsted acid sites was employed for direct glucose conversion into AcMF. Lewis acid sites of Sn-Mont facilitate the isomerisation of glucose to fructose. At the same time, dehydrative-esterification of fructose to AcMF is catalyzed by Bronsted acid sites of Sn-Mont. Different concentrations of Sn containing Sn-Mont catalysts were by prepared mixing montmorillonite clay with different molar concentration (e.g. 0.1 M-0.4 M) of aqueous solutions of SnCl4 center dot 5H(2)O. AcMF was produced in as high as 43% yield directly from glucose over Sn-Mont(0.3 M) catalyst owing to its highest acid strength. The efficacy of Sn-Mont(0.3 M) catalyst was also probed for sucrose and fructose that resulted in 53% and 58% yield of AcMF, respectively. The critical properties of all the prepared Sn-Mont catalysts were investigated through XRD, BET surface area, ICP-OES, temperature-programmed desorption of NH3 and pyridine-FTIR and XPS techniques.
Keywords: 5-(Acetoxymethyl)furfural; Bronsted/Lewis acid; carbohydrates; Dehydrative-esterification; Sn-Mont